Legal Protection of Abortion Perpetrators Due to Rape Crime in the Renewal of Criminal Law in Indonesia - Nabilla, Adinda; Rinwigati Waagstein, Patricia (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to analyze the legal protection of abortion perpetrators as a result of criminal acts of rape in the context of criminal law reform in Indonesia. Rape crimes are increasingly receiving public attention, with a significant increase in both number and impact. On the other hand, abortion as a social phenomenon continues to raise complex issues in the fields of medicine, law and ethics. Legally, abortion is considered a criminal offense, but there are exceptions in certain cases, such as for rape victims. This research takes a normative approach by analyzing current legal provisions, such as Article 428 of the Health Law and Article 116 of the Government Regulation on Health, which stipulate that abortion can only be performed in medical emergencies or for rape victims. The research findings show that although Indonesian law provides room for abortion in cases of rape, existing procedures are still limited and need to be reformed to provide better legal protection for victims. The conclusion of this research is that further revision of Indonesian criminal law is needed to ensure clearer and more effective protection for rape victims who are forced to have abortions.